A land more kind than home [compact disc, unabridged] - Cash, Wiley ([distributed by] Blackstone Audio, Inc., 2012)
Religion is supposed to shield children from the horrors of the world, but one Sunday nine-year-old Jess Hall secretly witnesses his autistic brother being smothered to death during a healing service at a little church in the mountains of North Carolina. Clem Barefield, the local sheriff, arrives to find a group of charismatic believers who have moved the boy's body and are unwilling to utter a word about his death. At the center of the mystery is Carson Chambliss, a snake-handling ex-convict turned preacher whose past is just as mysterious as the power he claims to possess.